2006
DOI: 10.1196/annals.1351.021
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Sex Hormone Metabolism

Abstract: The incidence of autoimmune diseases is higher in females than in males. In both sexes, adrenal hormones, that is, glucocorticoids, dehydroepiandrosterone (DHEA), and androgens, are inadequately low in patients when compared to healthy controls. Hormonally active androgens are anti-inflammatory, whereas estrogens are pro-inflammatory. Therefore, the mechanisms responsible for the alterations of steroid profiles in inflammation are of major interest. The local metabolism of androgens and estrogens may determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 23 publications
1
48
0
6
Order By: Relevance
“…This supports our findings with mouse microglial (BV2) cells showing a limited activity of 3␤-HSD/KSI, which is the rate-limiting enzyme for androgen (AD and T) synthesis [32]. This bi-functional enzyme responsible for the oxidation and isomerization of 5 -3␤-hydroxysteroid precursors into 4 -ketosteroids catalyzes the essential steps in the formation of most classes of active steroid hormones [33].…”
Section: Discussionsupporting
confidence: 75%
“…This supports our findings with mouse microglial (BV2) cells showing a limited activity of 3␤-HSD/KSI, which is the rate-limiting enzyme for androgen (AD and T) synthesis [32]. This bi-functional enzyme responsible for the oxidation and isomerization of 5 -3␤-hydroxysteroid precursors into 4 -ketosteroids catalyzes the essential steps in the formation of most classes of active steroid hormones [33].…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, the sex of the fetus being carried may influence the effect pregnancy has on the severity of asthma. Androgens have been shown to have anti-inflammatory effects [17] and spillover from a male fetus may protect the mother. Several studies have found that women pregnant with a female fetus are more likely to have increased symptoms during pregnancy than women pregnant with a male fetus [18•], although this does not appear to lead to more emergency department visits, as was shown in a recent paper [19].…”
Section: The Role Of Sex Hormones In Asthma Susceptibility and Severitymentioning
confidence: 99%
“…It has been shown that high physical activity is associated with lower levels of markers of inflammation (30). Estrogens have been shown to be proinflammatory (31); others have shown that certain estrogen, such as 17β-estradiol inhibits inflammatory gene expression that is regulated by nuclear factor κB (32). However, of interest is the observed pattern of associations; activity is most protective among those with normal body size and not exposed to estrogen.…”
Section: Discussionmentioning
confidence: 99%